Specific sex and gender factors of pericarditis in women. (25th November 2020) - Cepas Guillen, P.L; Martinez-Nadal, G; Izquierdo, M; Aldea, A; Matas, A; Lopez-Sobrino, T; Lopez-Barbeito, B; Andrea, R; Miro, O
Abstract: Introduction: Pericarditis is relatively common in clinical practice and may present as an isolated disease or as a manifestation of a systemic disease. There is an important sex-gap in the evidence on cardiovascular diseases, whereas it is unclear if there are sex-specific differences in the features of patients with acute pericarditis (AP). Objective: The aim of this study was to evaluate the presence of specific sex and gender factors of pericarditis in women. Material and methods: We retrospectively included all consecutive patients admitted with acute pericarditis (AP) in an emergency department (ED) of a tertiary care center between 2008 and 2018. Patients without acute pericarditis diagnosis criteria were excluded. We collected patients' baseline characteristics and management data. Recurrence and complicated related to AP at 30-days and 1-year follow-up were assessed. Results: A total of 729 patients (mean age 42±17.2 years, 33% females) were analyzed. Women were older than men (47.5 yo vs 40 yo, P<0.001). Univariate analysis showed that women presented more prevalence of obesity (11% vs 5%, P<0.01) and chronic kidney disease (6% vs 3%, P<0.05) with previous autoimmune disease (15% vs 3%, P<0.001), and previous immunosuppressive treatment more frequent (15% vs 7%, P<0.01). Women presented more delayed time between beginnings of symptoms until first medical attendance (70 min vs 41 min, P<0.01). No difference was found either echocardiography findings or blood test values. Autoimmune AP was more prevalent in women than men (9% vs 1%, P<0.001). Hence, corticosteroids treatment was more used in women (12% vs 4, 5%, P<0.001). In multivariate analysis, six factors were found as specific gender factors of pericarditis in women: Age (OR: 1.02, 95% CI: 1.01–13.2, P<0.01), obesity (OR: 2.27, 95% CI: 1.15–4.49; P<0, 05), smoker (OR: 0.39, 95% CI: 0.25–0.59, P<0.001), previous autoimmune disease (OR: 4, 29, 95% CI: 1, 77–13, 21; P<0, 01); electrocardiogram diagnosis criteria (OR: 0, 18, 95% CI: 0, 6–0, 52; P<0, 001); Autoimmune etiology (adjusted OR: 11, 78, 95% CI: 1, 99–69, 64; P<0, 01). No difference was found in recurrence of AP in 30-days and 1-year follow-up (12% vs 13%, P>0.05; 14% vs 13%. P>0.05; respectively). Conclusion: In our cohort, women with AP attended ED later than men and were less likely to present with typical AP changes in the electrocardiogram. Moreover, women are more commonly affected by specific forms of pericarditis related to autoimmune disease. However, follow-up did not show differences related to gender. Funding Acknowledgement: Type of funding source: None